How to Deduce Human Rights From Natural Law and Other Disciplines - Riofrío Martínez-Villalba, Juan Carlos (Universidad Hemisferios, 2023)
This research aims to detect the methodologies scholars use to conclude what is a human right or a natural right. For most of them, the mere citation of an article of the constitution or law does not provide enough justification for rights, and they usually resort to other supra-positive elements which are summarized in the